2018
DOI: 10.1111/hsc.12652
|View full text |Cite
|
Sign up to set email alerts
|

Zero-hour contracts and stress in UK domiciliary care workers

Abstract: The UK domiciliary care workers play a vital role in maintaining and improving the lives of service users who have a variety of needs. Around 60% of these employees work under zero-hours contracts but, while it is known that conditions such as temporary and shift working can influence employee health and performance, zero-hours have not been widely investigated. This project sought to first investigate the stress associated with working as a domiciliary care worker, as well as comparing the experiences of empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Workers also reported having experienced health related problems such as anxiety and stress which are aspects of mental health. Although these health-related issues could not be clinically proven as caused by ZHC, the findings support research by Ravalier et al [40] done in the care sector which found out that a greater proportion of care/support workers had worse mental health issues working on ZHC than those who had permanent contracts. However, workers experience different levels of stress and anxiety depending on the sector they work in.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Workers also reported having experienced health related problems such as anxiety and stress which are aspects of mental health. Although these health-related issues could not be clinically proven as caused by ZHC, the findings support research by Ravalier et al [40] done in the care sector which found out that a greater proportion of care/support workers had worse mental health issues working on ZHC than those who had permanent contracts. However, workers experience different levels of stress and anxiety depending on the sector they work in.…”
Section: Discussionsupporting
confidence: 82%
“…ZHCs pay significantly lower wage rates, approximately one-third lower than the average hourly wage among non-ZHC workers [30]. Ravalier et al [40] pointed out that ZHC has adverse effect on worker's job motivation [22], stress and influences worker's well-being. Ball et al [7] considered the extent to which agency workers and zero hours contracts were used in the UK and worker's vulnerability as a result of the Sports Direct zero-hour contract worker's abuse scandal.…”
Section: Introductionmentioning
confidence: 99%
“…-Insecure and precarious employment practices: Nearly half of the home care workforce in England are on a zero-hour contract, highest rate within the social care sector. Zero-hour contracts are a source of additional stress for home care workers (Ravalier et al, 2019). -Highest vacancy and turnover rates within the sector.…”
Section: Social Care In the Ukmentioning
confidence: 99%
“…Subsequent analyses focusing upon workers in social care present a mixed picture of the impact upon domiciliary care workers in the UK, probably due to differences in methodological approach. Prior to the COVID-19 pandemic, employment conditions such as zero-hours working and delivery context have received some attention in terms of domiciliary carer mental well-being [ 1 , 44 ]. Despite empirical occupational health research linking generic working demands (e.g.…”
Section: Discussionmentioning
confidence: 99%